Rituals for work : 50 ways to create engagement, shared purpose, and a culture that can adapt to change - Ozenc, Kursat, 1979-; Hagan, Margaret (John Wiley & Sons, Inc., 2019)
This book shows us how creative rituals can make our personal and business lives more meaningful and rewarding. --